Evaluation of the evolution of green management with a Kuhnian perspective - Samet Güner (Business Research, 2018)
The purpose of this study is to examine the evolutionary development of green management. To do this, first, Kuhn's 'paradigm' concept has been operationalized and the development stages of a movement of thought were determined. The green management is then scrutinized within the framework of each of these stages and the impacts of environmentalism in management research and practice are examined. It is concluded that the crises in normal science, existence of a scientific community, the presence of common beliefs, values and norms, and the increasing anomalousness are strengths of the green management. However, the core position of profit orientation in business strategies weakens the green management.
Keywords: 650; Green; Environment; Management; Paradigm; Profit; Kuhn